Enhancing MSME Income in North Sumatra through E-Accounting: Examining the Role of Accounting Literacy from a Maqasid al-Shariah Perspective - Arafah, Yenni; Soemitra, Andri; Nurlaila, Nurlaila (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
This study examines the impact of E-Accounting on the revenue of MSMEs in North Sumatra Province, addressing gaps in the existing literature regarding the role of accounting literacy. The study also explores the challenges faced by MSMEs in adopting E-Accounting. Using a mixed-methods approach with an exploratory sequential design, quantitative data were collected through structured questionnaires from 271 MSMEs across seven districts and cities and analyzed using PLS-SEM. Qualitative data were obtained through in-depth interviews with 20 purposively selected MSMEs. The results indicate that E-Accounting has a significant positive effect on MSME revenue; however, accounting literacy does not function as a significant moderating variable. This suggests that the benefits of E-Accounting in increasing revenue do not depend solely on users’ accounting knowledge. Qualitative findings reveal that although MSMEs acknowledge the benefits of E-Accounting, its use remains largely administrative rather than strategic. Key challenges include limited digital infrastructure, insufficient training, and a strong reliance on intuitive decision-making. The novelty of this research lies in the integration of Sharia principles, such as trustworthiness and the protection of wealth, providing insight into how Islamic values influence MSME financial practices. This study offers practical and culturally relevant recommendations to improve E-Accounting adoption and strengthen MSMEs’ financial resilience through the alignment of technology and ethical principles.